Design and construction of a wearable wireless electrogoniometer for joint angle measurements in sports (2017)
Advances in the field of biomedical engineering have allowed the development of biometric devices to evaluate sport performance. This article describes the design and construction of a wearable electrogoniometer to monitor joint angle in real time for sports applications. The electrogoniometer uses four accelerometers connected to a microcontroller. The joint angle is estimated and transmitted via Bluetooth Low Energy. This prototype is a low-cost, low-power, and comfortable to wear solution for joint angle measurement. © Springer Nature Singapore Pte Ltd. 2017.